Treatment of Anterior Crossbite with Inverted Bracket Position, Case Report - Ulfah, Khairiyah; Mulkhairul, Ilham; Andayani, Ridha (Journal of Syiah Kuala Dentistry Society, 2024)
Background: Anterior crossbite is an abnormality in the sagittal direction of one or more maxillary anterior teeth against the mandibular teeth. Although the incidence of this case is small, it can cause aesthetic problems, tooth abrasion, caries, gingivitis, bone resorption, and gingival recession. Case Report: A 24-year-old female patient presented with her upper front teeth positioned behind her lower teeth and a noticeable gap between her upper front teeth. She exhibited an anterior crossbite involving teeth 22 to 32, a central diastema, and crowding of the upper and lower front teeth. Treatment was carried out using a fixed orthodontic with an MBT system and the bracket placement of 22 in an inverted position to get a labial torque effect on the roots. Conclusion: The use of pre-adjusted brackets with the MBT system and the placement of the lateral incisive bracket in an inverted position successfully corrected the anterior crossbite in these teeth both at the crown and root without additional wire bending or auxiliary spring.